PERGESERAN BAHASA BUTON CIA-CIA PADA REMAJA DI DUSUN WARAU KECAMATAN HUAMUAL KABUPATEN SERAM BAGIAN BARAT: KAJIAN SOSIOLINGUISTIK - Tuanakota, Wandi; Susi Hardila Latuconsina; Wa Mirna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines the shift in the Butonese Cia-Cia language among teenagers in Warau Hamlet, Huamual District, West Seram Regency. The formulation of the research problem includes the pattern of use of the Butonese Cia-Cia language among teenagers and the factors that cause this language shift. The aim of this research is to describe the pattern of use of the Butonese Cia-Cia language and identify the factors that cause language shift among teenagers in Warau Hamlet. The research uses a qualitative descriptive method with stages of planning, preparation, implementation and data analysis. Data was obtained through collecting information from teenagers as research informants. The research results show that the use of the Butonese Cia-Cia language among teenagers is experiencing a shift. In the family environment, teenagers use Indonesian and the Ambon dialect more than Butonese Cia-Cia. In the community, the use of regional languages ​​is limited to maintain smooth communication and tolerance between residents. Meanwhile, in the school environment, the Butonese Cia-Cia language is not taught so its use is decreasing. Factors that cause language shifts include the lack of language inheritance from parents to children from an early age, the dominant use of the Ambonese dialect in daily life, and the influence of globalization which encourages the use of Indonesian and languages ​​that are more commonly used in social communication. Thus, the Butonese Cia-Cia language has experienced a decline in usage among the teenagers of Warau Hamlet.